Procedural consequences of the presumption of an employment relationship. Limits of the competent authority’s decision regarding the presumption and the extent of its binding effect on other authorities - Bartosiak, Kajetan; Dobrowolska, Martyna (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The authors analyze the procedural consequences of the presumption of an employment relationship arising from Directive (EU) 2024/2831 of the European Parliament and the Council, with particular emphasis on the restrictions of decisions made by competent authorities and their binding effect on other entities. The paper discusses the classification of employment status in the context of platform work, as well as the related obligations of employers and the rights of employees. Exceptional attention is given to procedural issues, such as the binding effect of labor court rulings, the possibility of rebutting the presumption, and the impact of such rulings on administrative and judicial proceedings in other areas of law. The authors highlight potential risks associated with the implementation of the presumption of an employment relationship in the Polish legal system and propose de lege ferenda recommendations, including the harmonization of relevant legal provisions.